การไฮโดรทรีตติ้งของน้ำมันปาล์มโอเลอิน ปาล์มสเตียริน และกรดไขมันปาล์ม โดยใช้ตัวเร่งปฏิกิริยานิกเกิลโมลิบดีนัม - ภาณุวิชญ์ เจริญวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To investigate catalytic hydrotreating reaction of palm olein, palm stearin and palm fatty acid distillate using nickel molybdenum catalyst. The experiments were conducted in a fixed bed continuous flow reactor. The pressure was maintained at 750 psig while the temperatures were varied at 200ºC, 250ºC, 300ºC and 350ºC and liquid hourly space velocity (LHSV) of 0.5, 1.0 and 1.5 hr-1 were used during the study. The results showed that at high reaction temperatures and low liquid hourly space velocity, the reactants converted to alkanes by hydrodeoxygenation reaction, decarboxylation reaction and decarbonylation reaction while only fatty acids were detected in products at low reaction temperatures